If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -1(-21) = x + -1(-19) Multiply -1 * -21 5x + 21 = x + -1(-19) Reorder the terms: 21 + 5x = x + -1(-19) Multiply -1 * -19 21 + 5x = x + 19 Reorder the terms: 21 + 5x = 19 + x Solving 21 + 5x = 19 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 21 + 5x + -1x = 19 + x + -1x Combine like terms: 5x + -1x = 4x 21 + 4x = 19 + x + -1x Combine like terms: x + -1x = 0 21 + 4x = 19 + 0 21 + 4x = 19 Add '-21' to each side of the equation. 21 + -21 + 4x = 19 + -21 Combine like terms: 21 + -21 = 0 0 + 4x = 19 + -21 4x = 19 + -21 Combine like terms: 19 + -21 = -2 4x = -2 Divide each side by '4'. x = -0.5 Simplifying x = -0.5
| -58=y/4 | | ((6-14)+4)*4= | | -58=-6y | | 5x-(21)=x-(-19) | | 14e^2+4x=112 | | x-(-5)=6x+10 | | 42/-6 | | a+b-a+2b= | | 1/5x+3=14 | | 4x^2-8x-77=0 | | 3x-(-1)=-16 | | 5+2y=6 | | 4x+6=24-2 | | 256*12x= | | 256*20= | | 5w-7w=4 | | 4z=1.8+3.8 | | 10/7*4 | | X-5x+3x-9x= | | 1.4(5x-.1)= | | 5/6k=7 | | -12-16*4= | | 4(z+6)-26= | | 4x/7x+28 | | 1-6x=19+3x | | 4x/27+8x | | 2(5z-1)-2(6-2z)=4 | | 3(2z-2)-3(5-3z)=3 | | 3y/4=0.6 | | 60-3(E-5)= | | -3x+8x^2+1=0 | | 3(r-4)=3 |